JOURNALISM IN TURKEY - Sa'dullayeva Madina Shermurodovna (Web of Journals Publishing, 2025)
In the Turkic language region, the field of journalism is moving towards its complex and multifaceted development. This field plays an important role not only as a means of dissemination of information, but also in the coverage of all aspects of the life of society. Journalism serves as the main tool in shaping the minds of the population, highlighting the changes that are taking place in areas such as culture, politics, economics, social life.
Keywords: Turkic languages, journalism, Press, society, culture, politics, economics, manipulation, modern demand, standards.